2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1327011
|View full text |Cite
|
Sign up to set email alerts
|

Improved linear crosstalk precompensation for DSL

Abstract: Crosstalk is the major source of performance degradation in next generation DSL systems such as VDSL. In downstream communications transmitting modems are co-located at the central office. This allows crosstalk precompensation to be employed. In crosstalk precompensation the transmitted signal is pre-distorted such that the pre-distortion destructively interferes with the crosstalk introduced by the channel.Existing crosstalk precompensation techniques either give poor performance or require modification of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 4 publications
1
35
0
1
Order By: Relevance
“…Let H(f ) be the channel matrix of p twisted pairs at frequency f . Let r(f ) = r(H(f )) as in (6). The transmission rate loss of the i-th user at frequency f due to quantization is bounded by …”
Section: Appendix H: Lifting the Assumption Of Equal Psd From Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Let H(f ) be the channel matrix of p twisted pairs at frequency f . Let r(f ) = r(H(f )) as in (6). The transmission rate loss of the i-th user at frequency f due to quantization is bounded by …”
Section: Appendix H: Lifting the Assumption Of Equal Psd From Thmentioning
confidence: 99%
“…In [2], [3] it is shown that optimal cancelation achieves capacity boost ranging from 2× to 4×, and also substantially reduces per-loop capacity spread and outage, which are very important metrics from an operator's perspective. References [5], [6] advocate the use of a diagonalizing precompensator, and demonstrate that, without modification of the Customer Premise Equipment (CPE), one can obtain near optimal performance. Recent work in [7], [8] has shown that a low-order truncated series approximation of the inverse channel matrix affords significant complexity reduction in the computation of the precoding matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For the loop lengths considered here (up to 590 m), IL is at least 30 dB less than FEXT attenuation. The matrix is therefore diagonally dominated, and it is possible to pre-equalize it at the transmitter's side without a significant penalty 3 in terms of transmission power [3]. Thus, upon premultiplication by (5) the effective MIMO channel-transfer matrix becomes (6) Note that we do not invert the direct IL channels; that would entail a significant power penalty, especially at higher frequencies.…”
Section: Capacity Evaluation Methodsmentioning
confidence: 99%
“…The normalized receiver error signal can be expressed by (4) For a given line , a key performance measurement obtained via standardized mechanisms is an SNR estimate , where (5) Since the transmit power is known precisely, an estimate of is equivalent to an estimate of . In order to drive the residual matrix to zero, we must manipulate the precoder matrix , without a priori knowledge of the channel matrix .…”
Section: A Controlling the Residual Matrixmentioning
confidence: 99%